Tren Penelitian Anggaran di Indonesia - Rahmawati Setyo Wigati; Doddy Setiawan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
This study aims to provide an overview development of budgeting research in Indonesia. The study was taken from 19 accredited journals in Indonesia. Research samples were obtained from 2008 to 2018 and 74 articles were discussed on budgeting. This study classified the articles based on the sectors of reasearch, research methods and research variables used by the researchers. The most researched sector of the budgeing is in the public sector, while the most widely used method is the quantitative method. Whereas the most reasearch in independent variable is participation in budgeting, the dependent variable that is mostly studied is Performance because it is possible for a person's performance to depend on how the budget management is carried out.